Is abdominal wall hemorrhage an avoidable complication of robotic radical prostatectomy? (Annals of Medical Research, 2021)
Aim: We presented the diagnosis and treatment of patients with abdominal wall hemorrhage after robot-assisted laparoscopic radical prostatectomy (RALRP) in a high volume center. Materials and Methods: We retrospectively screened the data of 1950 patient RALRP series performed between June 2010 and December 2019 in our clinic. Patients who developed postoperative abdominal wall hemorrhage were included in the current study. The diagnosis of abdominal wall hemorrhage was established by ultrasonographic and physical examination findings. Results: In our 1950 patient RALRP series, 15 (0.7%) patients developed abdominal wall hemorrhage. The mean decrease in hemoglobin values was 3.9 (2.8-4.7) g/dl at postoperative 6th hour. On the postoperative 2nd day, areas of ecchymosis were observed on the abdominal wall skin. On the postoperative 4th day, hemoglobin level was stabilized. Blood transfusion was required for 8 of 15 patients. None of the patients required surgical exploration. At the postoperative 1st month control visits, we observed that the ecchymosis was completely disappeared. Conclusion: RALRP is a surgical technique that has been increasingly preferred in the treatment of localized prostate cancer. Abdominal wall hemorrhage is a rarely seen complication of RALRP that may be avoided by paying attention to some anatomical landmarks and optimizing the blood level of muscle relaxant medications at an effective dose. As a rerely seen complication of RALRP, abdominal wall hemorrhage can be successfully managed without the need for explorative surgery.
Keywords: Hemorrhage; prostate cancer; robotic surgical procedures